MODEL PEMBELAJARAN INKUIRI SOSIAL DALAM PEMBELAJARAN IPS (Harmony: Jurnal Pembelajaran IPS dan PKN, 2017)
Learning is successful when students are able to understand what they have learned. Before the teacher carries out the lesson, the teacher should plan the learning activities. One of them, the teacher must determine the appropriate learning model. Choosing the right learning model can make it easier for students to understand the subject matter. Learning social inquiry model can be developed by the teacher to proceed optimally and become an alternative IPS learning model that students are interested in. Pembelajaran dikatakan berhasil apabila siswa mampu memahami apa yang telah dipelajarinya. Sebelum guru melaksanakan pembelajaran, guru harus menyusun rencana kegiatan pembelajaran. Salah satunya, guru harus menentukan model pembelajaran yang tepat. Pemilihan model pembelajaran yang tepat dapat mempermudah siswa memahami materi pelajaran. Model pembelajaran inkuiri sosial dapat dikembangkan oleh pihak guru agar berjalan secara optimal dan menjadi alternatif model pembelajaran IPS yang diminati siswa.